2017
DOI: 10.1111/trf.14256
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Zika virus infectivity in platelet concentrates after treatment with ultraviolet C light and in plasma after treatment with methylene blue and visible light

Abstract: Our study demonstrates that the THERAFLEX UV-Platelets system and THERAFLEX MB-Plasma system can reduce ZIKV infectivity in PCs and pooled plasma to the detection limit of the assays used. These findings suggest both systems have the capacity to be an effective option to manage potential ZIKV transfusion transmission risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 36 publications
3
40
0
1
Order By: Relevance
“…Hemolytic and lipemic units were discarded. In accordance with the instructions for use of the THERAFLEX UV‐Platelets system, the target platelet concentration was 0.8 to 1.4 × 10/mL and the target plasma content was 30% to 40%. Air was removed from the containers and the PCs were UVC treated as described in detail below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolytic and lipemic units were discarded. In accordance with the instructions for use of the THERAFLEX UV‐Platelets system, the target platelet concentration was 0.8 to 1.4 × 10/mL and the target plasma content was 30% to 40%. Air was removed from the containers and the PCs were UVC treated as described in detail below.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that UVC treatment significantly reduces the infectivity of platelet products contaminated by disease‐causing bacteria, viruses, and protozoa. In addition, THERAFLEX UV‐Platelets inactivates contaminating donor WBCs while preserving platelet function and coagulation factors …”
mentioning
confidence: 99%
“… The UVC transparency of the irradiation bags was increased during the development of the THERAFLEX UV‐Platelets system. The inactivation efficacy of a UVC dose of 0.2 J/cm 2 used as full dose in this study and other recent studies , is equivalent to a UVC dose of 0.3 J/cm 2 used in the early phase of development , …”
Section: Discussionmentioning
confidence: 51%
“…10 This system has been tested in various studies against a wide range of disease-causing viruses, bacteria, and protozoa. 8,[11][12][13][14][15] In particular, the UVC-based PI system was effective against porcine parvovirus (PPV) and encephalomyocarditis virus (EMCV), 7 two nonenveloped viruses listed among those model viruses recommended for the evaluation of pathogen inactivation and removal technologies. 16,17 Its efficacy against PPV and EMCV suggests that THERAFLEX UV-Platelets may also be able to inactivate other nonenveloped viruses.…”
Section: Conclusion: Theraflex Uv-platelets Effectivelymentioning
confidence: 99%
“…Andere umhüllte Viren wie Dengue Virus (DENV) 1-4, ChikungunyaVirus (CHIKV), Ross River Virus (RRV) und Zikavirus (ZIKV) wurden ebenfalls gut inaktiviert [128,131].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified